Depressive symptoms in patients with heart failure negatively affect family caregiver outcomes and quality of life. (1st February 2016) - Chung, Misook L; Lennie, Terry A; Mudd-Martin, Gia; Dunbar, Sandra B; Pressler, Susan J; Moser, Debra K
Abstract: Background: Depressive symptoms in people with heart failure (HF) are highly prevalent. Caring for patients with both HF and depression may be more burdensome than caring for patients with HF alone. Aims: The purpose of this study was to examine differences in caregivers' outcomes (i.e. caregiving burden, difficulty and time spent on caregiving, perceptions of life change as a result of caregiving, and quality of life) between caregivers who take care of HF patients with depressive symptoms and without depressive symptoms. Method: Patient-caregiver dyads at an outpatient clinic completed survey questionnaires. Patients' depression was assessed using the Beck Depression Inventory-II (BDI-II); primary caregivers completed caregiving outcome questionnaires. Differences in caregiving outcomes between patients with and without depressive symptoms (BDI-II≥14) were examined using t -tests, Chi-square, and Mann-Whitney U-test. Results: Of 102 patients (64% male, mean age 61, 41% NYHA Class III–IV, mean ejection fraction 35.8±13.9), 26.5% had clinically significant depressive symptoms. Of the primary caregivers (78% female; mean age 56.7), 42% reported severe burden (the Zarit Burden Interview (ZBI)≥17). Caregivers of patients with depressive symptoms had a higher level of burden (25±13 vs 13.5±12 on the ZBI; p <0.001), spent more time caregiving (37±12 vs 30±11 on the Oberst Caregiving Burden Scale; p =0.004), and reported worse mental quality of life (46±10 vs 51±10 on the SF-12v2; p =0.026) than those of patients without depressive symptoms. Conclusion: Family members caring for HF patients with depressive symptoms had significantly higher levels of caregiving burden and worse quality of life compared to those caring for patients without depressive symptoms.